Experimental investigations on substitution of natural sand in concrete with copper slag and blast furnace slag - Ojha, P N; Singh, Abhishek; Singh, Brijesh (Journal of Asian Concrete Federation, 2021)
The constant decrease in the availability of good quality natural sand across the globe has led to increasing investigations on the possibility of utilizing by-products obtained from different industries as a replacement for natural sand. Copper slag and blast furnace slag are by-products of metallurgical processes occurring during copper and pig iron production, respectively. The substitution of natural sand using copper slag and blast furnace slag in plain and reinforced concrete has been permitted in Indian Standard IS: 383-2016 up to a certain percentage as replacing natural sand in concrete. In the present study, investigations were carried out to check the feasibility of increasing copper slag and blast furnace slag as a substitution of natural sand in concrete. Conventional (Natural) sand was replaced (by volume) with copper slag (0%, 25%, 50% & 75%), Granulated Blast Furnace Slag (GBFS) (0%, 30%, 60% & 100%) and Air-Cooled Blast Furnace Slag (ACBFS) (0%, 30%, 60% & 100%). Concrete mixes were examined by substituting conventional sand with copper and blast furnace slag in different proportions and were evaluated for different mechanical properties and durabil-ity-related parameters. Leaching studies were also carried out on selected concrete samples.